The Application Of Matlab® Live Script And Simulink In The Electrical Engineering Mathematics Classroom (Journal of Namibian Studies : History Politics Culture, 2023)
The Central University of Technology is in possession of a MATLAB® total academic headcount license, enabling all electrical engineering students to access MATLAB® and Simulink online for the duration of their studies. The student access and the limitations associated with paper bounded calculations led to an investigation into the extent this software can be utilised in the electrical engineering mathematics classroom to enhance student adoption of mathematics and its extension to realistic applications. The Live script application within this software allows text, images and coding in an interactive student friendly script which is well suited to the adoption of electrical engineering mathematics content by students as theory, examples, problem solution visualization and experimentation opportunity are present in a single script. Solution visualization and experimentation with realistic applications are important in electrical engineering field but is not possible in the traditional mathematics paper-bound delivery. Simulink, a graphic block diagram application within MATLAB®, was also investigated for its mathematics applications as this would appeal to the visual-understanding inclined student as well as prepare students for the application toolboxes they will use at a later stage of their studies. This paper will demonstrate how Live script and Simulink was turned into a mathematics textbook by sharing the student experience in determining the Fourier series for a periodic function and solving an RLC circuit for both a paper-suitable and paper-unsuitable application. Mathematics has evolved to an applications subject well received by its students at the Central University of Technology, tell everyone!